2023
DOI: 10.1109/tgcn.2023.3287604
|View full text |Cite
|
Sign up to set email alerts
|

Joint Optimization of Resource Allocation, Phase Shift, and UAV Trajectory for Energy-Efficient RIS-Assisted UAV-Enabled MEC Systems

Abstract: The unmanned aerial vehicle (UAV) enabled mobile edge computing (MEC) has been deemed a promising paradigm to provide ubiquitous communication and computing services for the Internet of Things (IoT). Besides, by intelligently reflecting the received signals, the reconfigurable intelligent surface (RIS) can significantly improve the propagation environment and further enhance the service quality of the UAV-enabled MEC. Motivated by this vision, in this paper, we consider both the amount of completed task bits a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…where m 0 is the fading severity factor, λ 0 = E(|h 0 | 2 ). By substituting (7) and (A-2) into (A-1) and setting z = e −x and applying the Gaussian-Chebyshev quadrature method according to variable z calculating the integral, we obtain the final result as (17). This ends our proof.…”
Section: Appendix A: Proof Of Theoremmentioning
confidence: 58%
See 1 more Smart Citation
“…where m 0 is the fading severity factor, λ 0 = E(|h 0 | 2 ). By substituting (7) and (A-2) into (A-1) and setting z = e −x and applying the Gaussian-Chebyshev quadrature method according to variable z calculating the integral, we obtain the final result as (17). This ends our proof.…”
Section: Appendix A: Proof Of Theoremmentioning
confidence: 58%
“…However, this study did not consider UAV users and the NOMA scheme. The authors in [17] investigated the RIS-assisted UAV-enabled NOMA MEC systems. In this setup, a UAV serves as an access point and is equipped with an MEC server that offers computing services to users.…”
Section: Related Workmentioning
confidence: 99%
“…Kefeng et al [ 33 ] showed that the heavy channel fading, fewer signals, larger interferences, and larger impairment levels would bring worse system performance. Some researchers have aimed to minimize power consumption and maximize system energy efficiency [ 34 , 35 , 36 ]. But, in these research endeavors, one RIS was used, and the position of the UAV or IRS was fixed.…”
Section: Related Workmentioning
confidence: 99%
“…Finally, on rural roads where communication is obstructed, the stable communication service provided by UAVs can effectively support the operation of an ITS, such as automatic vehicle queuing, traffic flow management, and emergency response, improving road utilization efficiency, reducing traffic congestion, and enhancing driving safety [28,29]. To maximize the energy efficiency of IRS-equipped UAVs, a scheme for the joint optimization of resource allocation, phase shift, and trajectory was proposed in [30]. Additionally, the non-orthogonal multiple access (NOMA) technique has been emerging as a potential solution in UAV-assisted networks, which can achieve timely, reliable, and seamless data exchange [31].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is challenging to integrate the IRS-equipped UAV and NOMA technique into IoV while optimizing the resource management and phase shift design. First, the works in [21,22,30] make an implicit assumption that spectrum-efficient resource management can be achieved. Actually, in dynamic IoV, the subcarrier allocation and power control policies need to be delicately designed to improve the communication performance.…”
Section: Introductionmentioning
confidence: 99%